Sculpteurs d’une cause perdue : statues et causes d’une perte ? - Véronique Ha Van (Transatlantica)
In the conversations that Confederate statues have provoked, little attention, if any, has been paid to the authors of those statues. These artists willingly participated in the commemorative movement that is so highly contested today; they also gave shape to the generals and soldiers that the Lost Cause advocates honored and sited in public places. In order to grasp the process that led to the monumentalizing of the late-nineteenth- and early-twentieth-century South and thus in part help us to understand the ramifications of the very existence of those works in today’s world, this article looks at a number of these artists—Antonin Mercié, Alexander Doyle, Frederick W. Ruckstull, Alexander Phimister Proctor—as well as the procedures which led to their selection.